A mixed method inquiry of early complementary feeding of infants in the Dominican Republic. (1st March 2022) - McLennan, John D.; Pérez Agramonte, Miki; Mosquea Hernández, María
Abstract: Exclusive breastfeeding (EBF) is infrequent and decreasing over time in the Dominican Republic. This study aimed to identify patterns of, and women's rationale for, early complementary feeding. Mothers of children under 12 months of age living in a low-resource peri-urban community had three opportunities to contribute: (i) responding to feeding questions embedded in a standardized questionnaire used at a well-baby clinic (n = 101), (ii) participating in focus groups (n = 31), and (iii) engaging in home-based, semi-structured individual interviews (n = 25). Quantitative questionnaire data were analyzed to identify feeding practices as a function of child age. Textual data from the individual interviews and focus groups were systematically reviewed and coded to identify key constructs through a qualitative descriptive approach. The majority (>86%) of mothers reported breastfeeding at all monthly age bands up to six months. However, EBF was rare, with more than half reporting use of other milks and other foods by the infants' second and fifth month, respectively. Overarching themes to explain early complementary feeding from the qualitative data can be broadly captured by the complementary perceptions that there are problems with relying on breastfeeding alone and that there are benefits to early complementary feeding in the early months of an infant's life. EBF was experienced as (A) insufficient, (B) not always available, (C) sometimes not safe, (D) having potentially negative effects on the mother, and (E) bringing challenges. Complementary feeding was identified as helpful in addressing each of these concerns. Although mothers typically endorsed breastmilk as the preferable and best option for infant feeding, this did not translate into EBF and was not presented as contradictory to the use and perceived benefits of early complementary feeds.